Meteorological Factors and Air Pollutants Contributing to Seasonal Variation of Acute Exacerbation of Atrial Fibrillation: A Population-Based Study. Issue 12 (December 2018) - Ahn, Jinhee; Uhm, Taewoong; Han, Junhee; Won, Kyung-Mi; Choe, Jeong Cheon; Shin, Ji Yeon; Park, Jin Sup; Lee, Hye Won; Oh, Jun-Hyok; Choi, Jung Hyun; Lee, Han-Cheol; Cha, Kwang Soo; et al.
Abstract : Objective: We investigated seasonal variation of acute exacerbation of atrial fibrillation (AAF) and contributing environmental factors. Methods: AAF events, meteorological elements, and air pollutants in Seoul between 2013 and 2015 were obtained from the nationwide database. AAF was defined if a patient visited the emergency room due to any AF-relevant symptoms or signs. Results: AAF occurred less frequently in summer than in other seasons (6.71 vs 7.25 events/d, P  = 0.005). AAF tended to decrease with an increase of air temperature ( r  = –0.058). Among air pollutants, NO2 was significantly lower in summer and positively correlated with AAF after adjusting for other variables ( β  = 3.197). Conclusions: The rate of AAF events was the lowest in summer; air temperature and NO2 were contributing factors. The weather and environmental conditions should be considered as risk factors of AAF. Abstract : Supplemental Digital Content is available in the text